Nurses' Knowledge toward Care of Unconscious Adult Patients at Teaching Hospitals in Al-Hilla City - kheder, nael; mohammed, widad (Iraqi National Journal of Nursing Specialties, 2019)
Objective: The study aims to evaluate nurses' knowledge toward care of unconscious adult patients and identify the relationship between nurses’ knowledge toward care of unconscious adult patient and their demographic characteristics of age, gender, Marital Status, level of qualification and years of experience. Methodology: A descriptive study (quantitative design) was carried out by using quasi experimental design to study nurses' knowledge, attitudes and practices toward care of unconscious adult patients at teaching hospitals in Al-Hilla City from September 2018 up to June 2019. A purposively sample has been chosen in which included 60 nurses who work in ICUs within two hospitals (Imam Al-Sadiq teaching hospital and Al-Hilla general teaching hospital). The sample has been collected by using the tool that involves four parts. The first part is demographical data for a study sample which consists of 10 items, the second part is multiple choice questions related to nurses' knowledge which consists of 32 items, The tool has been validated by 11 experts, all of them have experience more than 10 years, a reliability is determined by Crohn Bach correlation where r= 0.92 . The analyzed data have been stated during using of descriptive statistics (frequencies, percentages, mean of scores, Standard deviation) and inferential statistics (Coefficient alpha correlation and ANOVA). Results: The study showed that the majority of the participants in the study were males aged between 20-29 years of bachelor's degree in nursing. More than half of them were single and had years of experience in hospital and in intensive care unit (1-5) years, and half of the participants were doing their work in the morning and evening, within 24 hours, and the majority did not participate in training sessions on the intensive care unit. The study also showed that nurses' knowledge toward care of unconscious adult patients was enough. Recommendations: Advanced video programs, specific meetings, programs, workshops, training activities and seminars, and Booklet are should be provided for nurses on how to care of unconscious adult patients to increase their knowledge, it's recommended to the Ministry of Health to provide the necessary advanced supplies and equipment for use in intensive care units (ICUs) and It is recommended for future studies conduction.